Ideologi Media Dan Framing Pada Pemberitaan Perusakan Rumah Ibadah Di Kompas Dan Republika - Farid Muthaqin; Hamdani M. Syam; Putri Wahyuni (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2021)
This study aims to find out how the framing in the news related to the destruction of the Musala in North Minahasa on the news of online media Kompas.com in the period 30 January to 13 February 2020 and Republika.co.id for the period 30 January 2020 to 12 February 2020. This study uses a qualitative method. descriptive analysis with framing analysis by Robert N. Entman with four elements, namely defining the problem, diagnosing the cause, making moral judgments, and recommending treatment. This study focuses on news about the destruction of the Musala that occurred in North Minahasa. The results show that the framing of the news presented by Kompas.com media is objectivity in reporting the case of the destruction of the Musala in North Minahasa, by not taking sides with certain groups, as well as in explaining that Kompas.com refrains from writing in a safe style, as well as a narrow news perspective. while Republika.co.id is more daring in conveying facts and news that are presented in depth and viewed from various perspectives so that it is possible to find the aspirations of Muslims to get the right to get a Musala as a place of worship. The difference in the frame of the two media is influenced by the ideological factors of each media. Even though they have different framing, these two media want the incident of vandalism of places of worship in North Minahasa to be resolved peacefully.